2021
DOI: 10.3389/fpsyg.2021.717402
|View full text |Cite
|
Sign up to set email alerts
|

“Project for a Spatiotemporal Neuroscience” – Brain and Psyche Share Their Topography and Dynamic

Abstract: What kind of neuroscience does psychoanalysis require? At his time, Freud in his “Project for a Scientific Psychology” searched for a model of the brain that could relate to incorporate the psyche’s topography and dynamic. Current neuropsychoanalysis builds on specific functions as investigated in Affective and Cognitive (and Social) Neuroscience including embodied approaches. The brain’s various functions are often converged with prediction as operationalized in predictive coding (PC) and free energy principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…Instead of characterizing the brain and self by specific functions of single regions/networks, temporospatial neuroscience explores the spatial topography and temporal dynamics of neural activity and subjective mental contents. Spontaneous activity is topographically identified within interacting networks like default-mode, salience, and central executive network and is temporally characterized by the balance between infraslow, slow, and fast frequencies ( Northoff and Scalabrini, 2021 ).…”
Section: Temporospatial Neuroscience Of Brain and Selfmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead of characterizing the brain and self by specific functions of single regions/networks, temporospatial neuroscience explores the spatial topography and temporal dynamics of neural activity and subjective mental contents. Spontaneous activity is topographically identified within interacting networks like default-mode, salience, and central executive network and is temporally characterized by the balance between infraslow, slow, and fast frequencies ( Northoff and Scalabrini, 2021 ).…”
Section: Temporospatial Neuroscience Of Brain and Selfmentioning
confidence: 99%
“…The neural correlates of the self can be conceptualized under a spatially nested hierarchy in which brain regions (i.e., bilateral insula), of lower layers (e.g., interoceptive processing), are recruited again and complement additional regions within higher layers of the cognitive self ( Qin et al, 2020 ; Northoff and Scalabrini, 2021 ). Conducting a large-scale meta-analysis, Qin et al (2020) observed three levels of self.…”
Section: Temporospatial Neuroscience Of Brain and Selfmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent contributions conceive the self as a multilayered construct which originates in the course of the development, drawing on different sources of internal and external information, and also recruiting diverse brain structure into a progressively integrated complex neural network ( Northoff and Scalabrini, 2021 ; Qin et al, 2020 ). Assuming this perspective, the large-scale meta-analysis on neuroimaging studies by Qin et al (2020) proposes a nested hierarchy model of self which includes three intimately connected layers of processing: interoceptive-processing, exteroceptive-processing, and mental-self-processing.…”
Section: A Neuroscence Perspective Of Intersubjectivitymentioning
confidence: 99%